Development of Single Phase FEFSM and its Excitation Circuit for Evaluating the Control Algorithm - Amin, F.; Sulaiman, E.; Utomo, W.M.; Soomro, H.; Omar, F.; Kumar, R. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Popularity of Field Excitation Flux Switching Motors (FEFSMs) has been significantly increased in modern high-speed applications due to their features such as variable flux control and the rotor structure which is free from any magnet and windings. However, most of the FEFSM structure is comprising of overlapped windings between the armature and field teeth which ends up in taking more space, more copper losses and increasing material costs as well. This paper emphasis on a particular structure of single phase FEFSM having a segmented rotor and non-overlapped stator windings. This structure offered more efficiency and eliminated all the drawbacks mentioned above of having overlapped windings. Design of this new topology and its characteristics such as speed, torque, and power has been analyzed through a 2D Finite Element Analysis (FEA) using JMAG Designer. The proposed FEFSM shows drastic improvements in terms of flux production, torque and power performances in contrast with FEFSM with salient rotor structure. Furthermore, a very efficient control strategy is proposed for this new FSM topology. Since existing technics require high-end DSPs and expensive sensors, however, the proposed strategy can be implemented in any 8-bit microcontroller and only need Infrared transceiver sensor, which is more appropriate for developing a low-cost drive for house hold applications.